HUMAN RESOURCE DEVELOPMENT STRATEGY IN OPTIMIZING THE QUALITY OF EDUCATION AT KUTTAB AL FATIH DEPOK - Ferdianza, Yan; Muhammad Danial, R. Deni; Sunarya, Erry (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
To measure the quality or quality of education in each country, one of them is through PISA conducted by The Organization for Economic Co-operation and Development (OECD). The 2022 Programme for International Student Assessment (PISA) report 2018 – 2022 released in early December 2023 shows that the quality of Indonesian education occupies the 63rd position out of 81 countries. This shows that the quality of Indonesian education is still low. The purpose of this study is to describe the strategy of human resource development in improving the quality of education at Kuttab Al Fatih Depok. This research uses a qualitative descriptive method using case study research. The results of the study stated that to prepare qualified teachers, Kuttab Al Fatih Depok held the I'dad Mudarrisin Academy program for teacher education for 2 years before being placed in Kuttab Al Fatih. Meanwhile, Kuttab Al Fatih Depok's strategy is to develop its organization by establishing closeness in the vision and mission of the institution to parents. For the development of human resources in optimizing the quality of education in Kuttab Al Fatih Depok through weekly training and providing educational scholarships such as Family Academy, Qur'an Academy, and Siroh Academy. By participating in the program, quality human resources are produced and have an impact on the quality of education at Kuttab Al Fatih Depok, namely the fulfillment of the target of graduates of at least 7 juz of Qur'an memorization.